Inclusion of dehydrated mixture made of salmon and tilapia carcass in spinach cakes - Goes, Elenice Souza dos Reis; Souza, Maria Luiza Rodrigues de; Kimura, Katia Setsuko; Coradini, Melina Franco; Verdi, Rafaela; Mikcha, Jane Martha Graton (Acta Scientiarum. Technology, 2016)
The present study deals with dehydrated mixture of salmon (20%) and tilapia (80%) at 0, 5, 10 and 15% inclusion levels in spinach cake, and evaluates its proximate composition, sensory and microbiological characteristics. It was included 0, 5, 10 and 15% of the dehydrated mixture in the dough of the cake. Moisture and lipid contents were not modified (p >0.05) when the mixture was included in the cake. There was a positive linear effect for crude protein (y=6.24 + 0.29x, RÂ²=0.77) and mineral Â (y=0.60 + 0.19x, RÂ²=0.85). Carbohydrate and calorie contents decreased linearly (p <0.01) according to increasing levels of the mixture in the cake. With regard to sensory analysis, there was a negative linear effect for taste (y=7.48 - 0.07x, R2=0.98), texture (y=7.48 - 0.047x, R2=0.93), acceptance Â (y=7.13 - 0.046x, R2=0.99) and purchase intention (y=3.82 - 0.039x, R2=0.93), demonstrating that increasing levels of inclusion of the dehydrated mixture caused a decrease in the acceptance of the cake. It can be concluded that the inclusion of up to 15% of salmon and tilapia dehydrated mixture in spinach cake increases the contents of crude protein and mineral matter, and reduces the carbohydrate content and calorie. However, based on the sensory results, it is recommended to include 10% of the dehydrated mixture of fish in the spinach cake. Â